The Roberts Court and Oral Arguments: A First Decade Retrospective - Timothy R. Johnson; Ryan C. Black (Washington University Journal of Law & Policy, 2017)
This Article summarizes some prominent data points of the Roberts Court justices’ behavior during oral arguments at the Supreme Court. Johnson relays accounts from observers who have recognized an increase in questioning from the justices during oral arguments. The Articles suggests this increase may be attributed to the more talkative style of newer justices, as well as the changing role of the questions during oral arguments, which can inform the justices about their fellow judges’ thoughts and opinions. The Article concludes that these trends in questions, number of words spoken, and interruptions are likely to change as more attention is placed on the importance of oral arguments.
Keywords: Supreme Court; Roberts Court; Oral Argument; Retrospective; Behavior; Study; Questioning; Interpretation